Melamine-Ceramic Membrane for Oily Wastewater Treatment - Ossman, M.E.; Wagdy, W.; Nabat, K.Y.; Bramoo, A.; Mohamed, Y.; Gamal, M. (Journal of Membrane and Separation Technology, 2019)
Four distinctive Ceramic membranes have been synthesized using bentonite and Egyptian clay with the expansion of melamine. The addition of melamine (~ 1% by wt.) enhanced the porosity, density, the thermal stability and water permeability of the membranes made from bentonite or Egyptian clay while decreasing the chemical stability of either bentonite or Egyptian clay membranes. The most noteworthy level of decrease in COD (94.7%) is acquired for the concentration of 200ppm with saturating flux of 4.63 E-05 (m3/m2.s) utilizing (B+M) membrane. The cost of the four manufactured clay membranes was assessed based on raw materials used in the present investigation.